Culture and the cross-country differences in the gender commuting gap: Evidence from immigrants in the United States - Miriam Marcén; Marina Morales (Global Labor Organization (GLO), 2021)
This paper explores the role of the gender equality culture in cross-country gender commuting gap differences. To avoid inter-relationships between culture, institutions, and economic conditions in a simple cross-country analysis, we adopt the epidemiological approach. We merge data from the American Time Use Survey for the years 2006–2018 on early-arrival first- and second-generation immigrants living in the United States with their corresponding annual country of ancestry's Gender Gap Index (GGI). Because all these immigrants (with different cultural backgrounds) have grown up under the same laws, institutions, and economic conditions in the US, the gender differences among them in the time devoted to commuting to/from work can be interpreted as evidence of the existence of a cultural impact. Our results show that a culture with more gender equality in the country of ancestry may reduce the gender commuting gap of parents. Specifically, an increase of 1 standard deviation in the GGI increases women's daily commuting time relative to men by almost 5 minutes, a sizeable effect representing 23 percent of the standard deviation in the gender commuting gap across countries of ancestry. A supplementary analysis provides possible mechanisms through which culture operates and is transmitted, showing the potential existence of horizontal transmission and the importance of the presence of children in commuting. Our results are robust to the use of different subsamples, geographical controls, and selection into employment and telework.
Keywords: R41; J16; Z13; 330; Commuting; culture; immigrants; American Time Use Survey